2021
DOI: 10.33963/kp.a2021.0008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with arrhythmic mitral valve prolapse in a single tertiary center: prevalence of electrocardiographic and myocardial abnormalities

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially. Clinical characteristics of patients with arrhythmic mitral valve prolapse in a singletertiary center: prevalence of electrocardiographic and myocardial abnormalities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The main risk factors include leaflet thickness >5 mm, bileaflet prolapse, papillary muscle fibrosis, and mitral annular disjunction [1,2]. Zienciuk-Krajka et al [3] recently reported that among patients with arrhythmic mitral valve prolapse, survivors of cardiac arrest had a higher E/e' ratio. Myocardial work represents a relatively new echocardiographic parameter.…”
mentioning
confidence: 99%
“…The main risk factors include leaflet thickness >5 mm, bileaflet prolapse, papillary muscle fibrosis, and mitral annular disjunction [1,2]. Zienciuk-Krajka et al [3] recently reported that among patients with arrhythmic mitral valve prolapse, survivors of cardiac arrest had a higher E/e' ratio. Myocardial work represents a relatively new echocardiographic parameter.…”
mentioning
confidence: 99%
“…It has been proven that patients with Pickelhaube's sign are in higher risk group, which encounters VAs and has a visible focal fibrosis on CMR. The study of Zienciuk-Krajka et al [59], examined patients with malignant type of MVP. They were divided into two groups based on the occurrence of CA in their medical history.…”
Section: Picklehaube's Signmentioning
confidence: 99%
“…It is believed to result in a spontaneous diastolic depolarization and an abnormal automaticity. The study of Zienciuk-Krajka et al [59] was the first research, which noted the association between a high E/e' ratio and the SCD risk.…”
Section: Picklehaube's Signmentioning
confidence: 99%
“…Since CMR is not a widespread diagnostic tool, finding noninvasive techniques easily performed in routine clinical practice, which could help identify MVP patients with a morphological substrate for VAs, is of great clinical importance [31]. Twodimensional (2D) transthoracic echocardiography is unquestionably the first-step imaging modality for MVP diagnosis, and assessing its structural characteristics [16,23,32]. The length of the MAD, curling visualization, and the Pickelhaube sign are proposed to be the feature of the arrhythmic MVP phenotype in standard 2D echocardiography [33,34].…”
Section: Introductionmentioning
confidence: 99%